International humanitarian law - Crawford, Emily (Writer on international law); Pert, Alison (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"Emily Crawford is a lecturer and Director of the Sydney Centre for International Law (SCIL). She teaches international law and international humanitarian law, and has delivered lectures both locally and overseas on international humanitarian law issues, including the training of military personnel"--
Includes bibliographical references and index.
SOL (Funded by UNHCR)
Book Finder
Keywords: Humanitarian law; Humanitarian law -- International cooperation; International law and human rights